Debitage Stylistic Variability at Cox Ranch Pueblo. (March 2013) - Williams, Justin P.; Duff, Andrew I.; Andrefsky, William
Abstract : This paper applies the method of stylistic flake analysis ofWilliams and Andrefsky (2011) to the analysis of debitage from two middens from Cox Ranch Pueblo, a late Pueblo II (ca. 1050–1130) period habitation site in west-central New Mexico. Previous research has suggested the multiethnic nature of site occupation based on the presence of two distinct methods for the manufacture of utilitarian ceramics and the site's location at the interface of two of the Southwest's traditional culture areas. This study samples debitage from two of the largest middens, each associated with a residential roomblock at the site, to determine if any of the stylistic trends found among the ceramic artifacts could be detected within the debitage from the site. Results show that there are in fact two different styles of flint knapping at the site, though both styles are present within each of the two midden assemblages. It is concluded that these two stylistic groups may relate to the two ethnic groups suggested to have co-resided at the site.